Aspectos que ecoam no chão da quadra: considerações acerca das formações em educação física inclusiva - NAYANE VIEIRA DE LIMA (2024)
The present research aimed to analyze the process of developing continuing education courses offered by the Department of Education of the city of Campo Grande to Physical Education teachers in its school network on the theme of inclusive education from cultural studies. Among the specific objectives are: a) to understand who are the professionals responsible for the development of continuing education courses; b) to analyze the understanding of managers about the concept of inclusion in school Physical Education; c) to verify the themes addressed in the training courses. The study is qualitative, descriptive-exploratory, and data collection was carried out in two stages, initially through a documentary research to find the proposals of continuing education courses and later interviews were conducted with six people responsible for the development and organization of training courses for Physical Education teachers of the Municipal Education Network of Campo Grande, Mato Grosso do Sul. Data analysis was performed through content analysis (Bardin, 2010). The results showed that the trainings are developed based on three criteria, namely: trainings organized taking into account the suggestions of teachers; trainings based on what was observed by management as weaknesses of teachers; and trainings based on the Common National Curricular Base. In addition, the documents pointed out that of one hundred and thirty-seven trainings carried out, five of them had in their titles mentions to Physical Education in an inclusive perspective. Regarding the interviewed professionals, we observed that the group is made up of cisgender, white and brown people, and without disabilities. About the homogeneity of the group, a direct influence on perceptions about the inclusion of people with disabilities was not observed. About the management team’s understandings of the concept of inclusion in school Physical Education, we noted that, although there is a consensus on the importance of coexistence and mutual learning between people with and without disabilities, the nuances in the expressions used may suggest the presence of perceptions that potentially favor segregation. In this sense, both the objectives of school Physical Education and the perception of inclusion showed influences from their respective initial formations, with the maintenance of developmentalist views, inclusive conceptions that distance themselves from current approaches and the segregation of inclusive themes in continuing education. This indicates the need for continuing education for the management team so that there are new perceptions and end segregating practices. Finally, referring to the themes addressed in the training courses, we can observe in the documents that the chosen themes emphasize the fulfillment of a curricular reference developed by REME, methods for structuring the plans and their applicability, ways to evaluate students and the bodily practices mentioned in the BNCC as well as their progressions.